State Lliability for Legislative Acts: The Italian Experience - Pizzorusso, Alessandro (2004)
This article examines the liability of the State for legislative acts, comparing the situation in France and Italy, with particular reference to the current situation in Italian doctrine and jurisprudence. In this context, the Italian experience shows that the civil liability of the State for legislative acts has undergone significant changes. The author mentions that the concept of 'unjust damage' has been broadened. Now, not only damage to subjective rights, but also damage to legitimate interests can give rise to compensation. This is thanks to a movement towards the protection of individual rights against state action. On the other hand, Italy's integration into the European Union and its accession to the European Convention on Human Rights has meant that Community law and international treaties take precedence over national legislation. This situation means that legislative acts are not only subject to the rigidity of the Italian Constitution, but must also be subordinated to Community law. Finally, it is emphasised that it is not enough for the State to violate the law in order to speak of civil liability, but it is necessary that this violation causes damage that is considered unjust. Moreover, this criterion of injustice must be assessed in accordance with article 2043 of the Italian Civil Code.